UPAYA PENELUSURAN SYUẐÛẐ DAN ʽILAL PADA HADIS - Nurul Huda (Holistic al-Hadis, 2015)
A research on Syuẑûẑ and ʽilal of hadith (prophetic tradition) is definitely important to conduct despite it is admitted by Maḥmûd al-Ṭaḥḥân in his Uṣûl al-Takhrîj wa Dirâsat al-Asânîd as a complicated subject for research. He frequently states that the subject is complicated (ṣaʽb) since it deals with the hidden character (ghâmiḍ) which influences how hadis is considered as ḍaʽîf. Syuẑûẑ and ʽilal of hadis can only be detected by those who are granted with deep and thorough knowledge.